PELATIHAN PENGOLAHAN DAN PENGEMASAN SELAI NANAS KEPADA IBU-IBU DASA WISMA KELURAHAN MOKOAU KOTA KENDARI - SULAWESI TENGGARA - Dhian Herdhiansyah; Marsuki Iswandi; Bahari; Muh. Syukri Sadimantara; Hadi Sudarmo; Nur Asyik (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract The training on processing and packaging of pineapple jam aims to make the group of women from the homestead Mokoau Village – Kendari City able to take advantage of the underutilized yard. The target is a change in paradigm and behaviour in utilizing yard land as additional income. In addition, new business opportunities will be created because they can produce agricultural products that provide added value and are environmentally friendly. The implementation of training on the processing and packaging of pineapple jam was carried out in 3 stages: (a) Socialization; (b) Providing material on entrepreneurial motivation, processing and packaging of pineapple jam; and (c) Training through hands-on practice. The training activities used the lecture method and interactive discussion, while the pineapple jam processing and packaging training was carried out using the demonstration method. Based on the results of the pineapple jam processing and packaging training activities that have been carried out in the show: (a) The understanding and interest of the women of the homestead women about entrepreneurship increased by 88.5 per cent; (b) The homestead women's understanding and knowledge of processing and packaging of pineapple jam increased by 86.5 per cent; and (c) The understanding and knowledge of the women of the homestead on the processing and packaging of pineapple jam increased by 89.5 per cent. Abstrak Kegiatan pelatihan pengolahan dan pengemasan selai nenas bertujuan agar kelompok ibu-ibu dasa wisma Kelurahan Mokoau – Kota Kendari dapat memanfaatkan pekarangan yang kurang dimanfaatkan secara optimal. Target yang akan dicapai adalah terjadinya perubahan paradigma dan prilaku dalam memanfaatkan lahan pekarangan sebagai tambahan pendapatan. Selain itu akan terciptanya peluang usaha baru karena mampu menghasilkan produk pertanian yang memberikan nilai tambah dan ramah lingkungan. Pelaksanaan pelatihan pengolahan dan pengemasan selai nanas dilakukan dalam 3 tahap: (1) sosialisasi; (2) pemberian materi tentang motivasi berwirausaha, proses pengolahan dan pengemasan selai nanas; dan (3) pelatihan melalui praktek langsung. Kegiatan pelatihan menggunakan metode ceramah dan diskusi interaktif, sedangkan pelatihan pengolahan dan pengemasan selai nenas dilaksanakan dengan metode demostrasi. Berdasarkan hasil kegiatan pelatihan pengolahan dan pengemasan selai nanas yang telah dilaksanakan menunjukkan: (1) pemahaman dan minat ibu-ibu dasa wisma tentang kewirausahaan meningkat sebesar 88,5 persen; (2) pemahaman dan pengetahuan ibu-ibu dasa wisma tentang pengolahan dan pengemasan selai nanas meningkat 86,5 persen, dan (3) pemahaman dan pengetahuan ibu-ibu dasa wisma tentang pengolahan dan pengemasan selai nanas meningkat sebesar 89,5 persen